2020
DOI: 10.1096/fasebj.2020.34.s1.05085
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the antidepressant‐like effect of repeated administration of Nigella fixed oil in rats

Abstract: Due to the confirmation of the therapeutic properties of oils extracted from Nigella, and the constraints associated with antidepressant prescriptions, the reliance on phototherapy seems to be beneficial. The objective of the present paper is to investigate the behavioral effect of Nigella fixed oil, as well as exploring the histopathological impact on the structure of the hippocampus after exposure to the Unpredictable Chronic Mild Stress procedure in rats. Animals were randomly divided into five groups of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Additionally, thymoquinone has neuroprotective effects against epilepsy, parkinsonism, and anxiety, and improved learning and memory [59]. Furthermore, thymoquinone has exhibited beneficial behavioral effects in rodents [11,[60][61][62]. For example, Kadil et al [60,61] demonstrated an NS treatment that resulted in a significant antidepressant-like effect in rats exposed to an unpredictable chronic mild stress procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, thymoquinone has neuroprotective effects against epilepsy, parkinsonism, and anxiety, and improved learning and memory [59]. Furthermore, thymoquinone has exhibited beneficial behavioral effects in rodents [11,[60][61][62]. For example, Kadil et al [60,61] demonstrated an NS treatment that resulted in a significant antidepressant-like effect in rats exposed to an unpredictable chronic mild stress procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, thymoquinone has exhibited beneficial behavioral effects in rodents [11,[60][61][62]. For example, Kadil et al [60,61] demonstrated an NS treatment that resulted in a significant antidepressant-like effect in rats exposed to an unpredictable chronic mild stress procedure.…”
Section: Introductionmentioning
confidence: 99%